Evaluación de la utilización del alginato de sodio en el tratamiento del agua de retrolavado para la empresa Emsertenjo ESP en el municipio de Tenjo Cundinamarca (2021)
The document focused on the evaluation of the activity of a natural coagulant agent (Sodium Alginate) for the backwash water treatment of the PTAP of the municipality of Tenjo, Cundinamarca. Currently the treatment plant has a treatment capacity of 79 lps of raw water, where 3% corresponds to backwash water, which is used to wash the filters of the plants, removing sedimentable particles composed of iron minerals. , Magnesium, calcium, Anthracite and sludge from the catchment wells. Initially, the document began with an analysis of the current state of the PTAP, supported by secondary information provided by the EMSERTENJO E.S.P. company, together with a physicochemical analysis of the backwash water with the support of the HIDROLAB S.A. laboratory. for current backwash water conditions.